Developing Graduate Profiles through Research Road Map - Sri Wigati; Hasan, Nurul Fatma; Rianto Anugerah Wicaksono (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Universities should guarantee that graduates are ready for the challenges of current life, work, and citizenship. Thus, universities should manage a myriad of priorities to ensure students’ success in life, work, and citizenship. The first step to take is developing graduate profile. This study aims to design a research road map to develop the graduate profiles of Bachelor of Sharia Economics (BSE) Study Program in UIN Sunan Ampel Surabaya. BSE has designed three graduate profiles: 1) Practitioners in Islamic finance; 2) Islamic finance & public policy analyst; and 3) Moslem entrepreneur. Therefore, BSE focused on three specializations: Islamic financial institution; Islamic economy & public policy; and halal industry and Islamic business. Islamic financial institution sub major has been designed to support the first profile, Islamic economy and public policy has been designed to support the second, while halal industry and Islamic business has been designed to support the last. These three specializations is strengthened by BSE research studies. BSE research studies were then strengthened by research road map. In other word, research road map was designed to develop research studies, and finally to develop graduate profiles of BSE.